1971
DOI: 10.1111/j.1469-8137.1971.tb02560.x
|View full text |Cite
|
Sign up to set email alerts
|

THE FIELD DISTRIBUTION OF INTERACTING STRAINS OF POLYPORUS SCHWEINITZII AND THEIR ORIGIN

Abstract: Summary The interaction phenomenon between cultures of Polyporus schweinitzii has been investigated and used to determine the natural distribution of different strains of this fungus in conifer plantations. The interaction behaviour of synthetic heterokaryons has shown that those derived from the pairing of completely unrelated basidiospores are those most likely to simulate the interaction potential of wild strains. The development of interacting strains from genetically complex polysporous mycelia is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…Carr. ), where the occurrence of single, unique genotypes within different individual trees has been taken as evidence of direct basidiospore infection of the roots (Barrett & Uscuplic, 1971), Evidence that basidiospores of Phanerochaete velutina can establish in leaf litter abutting a wood surface was provided during a study of fungal colonization of oak {Quercus robur L,) stumps, when it was noticed that the fungus established decay columns from the cut surface only when this was covered by a layer of leaf litter originating from a regrowth canopy (Rayner, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Carr. ), where the occurrence of single, unique genotypes within different individual trees has been taken as evidence of direct basidiospore infection of the roots (Barrett & Uscuplic, 1971), Evidence that basidiospores of Phanerochaete velutina can establish in leaf litter abutting a wood surface was provided during a study of fungal colonization of oak {Quercus robur L,) stumps, when it was noticed that the fungus established decay columns from the cut surface only when this was covered by a layer of leaf litter originating from a regrowth canopy (Rayner, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…O. Kuntze. Both authors concluded has emerged (Adams & Roth, 1969;Barret & that somatic incompatibility can be used in Suillus Uscuplic, 1971;Rayner & Todd, 1979; Anderson ei for determining individuality. Since meiotically a/., 1979; Adams, Todd & Rayner, 1981;Kile, 1983; derived spores from basidia are the only spores Stenlid, 1985;Rayner & Boddy, 1986;Chamuris & produced in S. bovinus, and most Basidiomycotina Falk, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly this occurs between monokaryons and results from either homo-or heterogenic incompatibility (Raper, 1966;Esser & Blaich, 1973). In a few cases, antagonism has also been observed between dikaryons where heterogenic incompatibility may also be implicated (Adams & Roth, 1967;Mounce, 1929;Campbell, 1938;Barrett & Uscuplic, 1971). The latter has only been demonstrated in culture, frequently between geographically separated isolates.…”
Section: Introductionmentioning
confidence: 99%